School Principal Program as a Manager in Improving the Quality of Education - Setiawan, Usep; Drajat, Drajat; Hermawan, Agus; Saodih, Cahya (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2022)
In order to carry out their roles and functions as managers, school principals have the right strategy to empower educational staff through cooperative cooperation, provide opportunities for educational staff to improve their profession and encourage the involvement of all educational staff in various activities that support school programs. The purpose of this research is to obtain objective information about: the role of the principal as a manager in improving the quality of education in school institutions. Schools that are able to develop their institutions as organizations by themselves need to disclose all information owned by schools. The role of the school principal is to provide staff with access to the information needed, and to delegate authority to use it. In an effort to support and facilitate the work of subordinates, Principals need to carry out their roles in accordance with their status as school leaders. Organizational development in schools, school principals really need to trust staff and give them full authority and power to carry out their job duties. This is inseparable from the important role of the school principal as a manager in institutional management who regularly plans, organizes, directs and oversees the work carried out by his work team in each institution.